Investigating the Post-Mortem Risk of Transmission of SARS-CoV-2 Virus in Cadaveric Tissues: A Systematic Review of the Literature - Matteo Antonio Sacco; Saverio Gualtieri; Aurora Princi; Maria Cristina Verrina; Angela Carbone; Lucia Tarda; Francesco Ranno; Santo Gratteri; Isabella Aquila (Microorganisms)
The emergence of SARS-CoV-2, responsible for the COVID-19 pandemic, has prompted extensive research into its transmission dynamics; yet, a critical aspect that remains underexplored is the post-mortem infectivity of the virus within cadaveric tissues. Understanding the mechanisms by which SARS-CoV-2 maintains infectivity after death is essential, as it raises significant concerns regarding public health and forensic practices. Research indicates that the virus can persist in various tissues, including lung, liver, and kidney tissues, with studies showing that factors such as the time elapsed since death, the presence of underlying health conditions, and environmental conditions at the time of death can influence the level of infectivity in deceased individuals. These findings are not only crucial for establishing safety protocols for forensic investigators who handle cadavers but also for informing public health guidelines that govern the management of bodies during and after outbreaks. As we investigate the implications of post-mortem SARS-CoV-2 infectivity, it becomes imperative to establish comprehensive protocols to mitigate risks associated with the handling and disposal of infected bodies, thereby protecting public health and ensuring the safety of those working in forensic environments. This paper aims to elucidate the mechanisms of infectivity in cadaveric tissues, explore the persistence of the virus in various tissue types, and assess the broader implications for public health and forensic investigations, ultimately contributing to a safer approach in dealing with COVID-19-related fatalities.